Personal and Collective Disability Identity Development - Curtis, Rebecca S.; Hall, Angie; Weaver, Sharon; Meyer, Jill (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2018)
The purpose of this paper is to explore how individuals with disabilities establish and maintain a social identity that incorporates meaning and context into a personal and collective perspective defined as disability identity. Beginning with a broad lens, the concepts of identity and social identity are explored. Theories and concepts that have shaped and refined the concept of social identity, specifically within a context of disability, are introduced. Disability Identity development is explored as to the key components and constructs that bring forth a comprehensive view of identity development for individuals with disabilities. Finally, these components are brought together within the context of Independent Living in order to show how this movement supports a positive, life-enhancing worldview of disability.